2019
DOI: 10.31616/asj.2018.0098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teriparatide on Subsequent Vertebral Fractures after Instrumented Fusion Surgery for Osteoporotic Vertebral Fractures with Neurological Deficits

Abstract: Study Design Retrospective case review. Purpose To assess the incidence and effect of teriparatide (TP) on subsequent vertebral fractures following a long-instrumented fusion surgery for osteoporotic vertebral fractures (OVFs). Overview of Literature TP treatment may be a useful strategy for patients with OVFs treated with a long-instrumented surgery. Methods Overall, 47 patients who underwent long-instrumented fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Previous studies have demonstrated the superiority of TP over BP in patients who have undergone conservative treatment for OVF according to bone union rates [12][13][14]. Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [15][16][17][18][19][20]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of BP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the superiority of TP over BP in patients who have undergone conservative treatment for OVF according to bone union rates [12][13][14]. Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [15][16][17][18][19][20]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of BP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [15][16][17][18][19][20]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of BP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16,19,20]. However, there is limited literature on the relationship between administration of these agents and mechanical complications after posterior fusion surgery for OVF.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the superiority of TP over BP in patients who have undergone conservative treatment for OVF according to bone union rates [14][15][16]. Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [17][18][19][20][21][22]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of TP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the superiority of TP over BP in patients who have undergone conservative treatment for OVF according to bone union rates [13][14][15]. Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [16][17][18][19][20][21]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of TP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [16][17][18][19][20][21]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of TP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16][17][18][19][20][21]. However, there is limited literature on the relationship between administration of these agents and mechanical complications after posterior fusion surgery for OVF.…”
Section: Introductionmentioning
confidence: 99%